The importance of education combined with tailored exercise in the health and wellness of older adults: a community case study - Brummett, Mindy; Oglesby, Chassiti; Barkus, Sarah; Wheelock, Nina Meg; Tate, Allison (Frontiers in Psychology, 2024)
Current literature states the importance of mental and physical health in combating the effects of metabolic syndrome; however, there is limited information on whether providing education on the syndrome along with mental and individualized physical exercises improves perceived confidence in the older adult population. A solution to this problem would be to provide a course to this population with a primary goal of education and exercise prescription. A community case study was implemented in the spring of 2024 with the purpose of measuring perceived confidence in metabolic syndrome, management of stress and anxiety, and how to move safely with exercise. Twenty-nine older adults with an average age of 76.1 years were recruited from a local senior citizen center. A course was given to the participants that included education and prescription of exercises tailored to the needs of the individual. Before and after the course, participants completed a confidence survey investigating their confidence in lowering the risk for metabolic syndrome, managing stress/anxiety, and understanding how to move safely with exercise. Regarding the post surveys, knowing how to lower the risk of metabolic syndrome increased by 46%, learning how to manage stress and anxiety increased by 50%, and understanding how to exercise safely increased by 41%. The data from this study suggests that providing education along with specific exercise prescription improved the participant's confidence in lowering their risk for metabolic syndrome, management of stress and anxiety, and how to move safely with exercise.